Supporting data for the publication' High-Level fermentative production of Lactic acid from bread waste under Non-sterile conditions with a circular biorefining approach and zero waste discharge - Cox, Rylan; Kumar, Vinod; Narisetty, Vivek; Salonitis, Konstantinos; Agarwal, Deepti; Ranade, Vivek V.; Nagarajan, Sanjay; Venus, Joachim (Cranfield University, 2022)
Bread waste (BW) is a severe solid waste management problem in Europe. The current study demonstrates an environment-friendly solution by valorising BW into lactic acid (LA) and the corresponding solid residues generated during hydrolysis and fermentation to biogas. To this end, BW was saccharified through acidic and enzymatic hydrolysis, and the hydrolysate obtained was used for LA fermentation under non-sterile conditions using thermophilic Bacillus coagulans DSM1. Maximum glucose concentration achieved during acid hydrolysis with 2% (v/v) acid loading and 20% (w/v) solid loading was 67.9 g/L glucose, with a yield of 0.34 g/g BW. The LA accumulated with concentrated BW acid hydrolysate was 102.4 g/L with yield and productivity of 0.75 g/g and 1.42 g/L. h, respectively. For enzymatic hydrolysis, three commercial amylase preparations (Amyloglucosidase, Spirizyme, Dextrozyme) were employed. The highest glucose release (98.6 g/L) and yield (0.49 g glucose/g BW) was attained with Dextrozyme from Novozymes. The fed-batch fermentation by B. coagulans was conducted, using commercial glucose and glucose-rich BW hydrolysate from Dextrozyme. The LA titer, yield and productivity obtained with pure glucose were 222.7 g/L, 0.92 g/g and 1.86 g/L.h, respectively, whereas BW hydrolysate (BWH) resulted in 155.4 g/L LA, with a conversion yield and productivity of 0.85 g/g glucose and 1.30 g/L. h, respectively. Further to the LA biosynthesis, the solid residues generated during hydrolysis and fermentation were subjected to biogas generation, resulting in 553 mL CH4/g volatile solids under batch mode. This massive LA titer amassed under non-sterile conditions and integrated biogas production using fermented residues demonstrates a high potential for an integrated biorefinery based on BW.
Keywords: 'lactic acid microbes'; 'Bacillus coagulans Strain'; 'Acid hydrolysis effects'; 'food waste management'; 'Anaerobic digestion'; 'non-sterile'; 'Biotechnology'